Изменение условий жизни и численности водоплавающих птиц при образовании Киевского водохранилища - Мельничук, В.А. (Вестник зоологии, 1967)
Before the preparation of the reservoir bed and inundation the numbers of waterfowl were conditioned primarily by the spring flood. As the preparatory work developed, independently of the nature of the flood, the number of nesting ducks greatly decreased. As the reservoir was filled the numbers of waterfowl reached the initial level and even exceeded it, despite the late spring flood due to the formation of the new basin and the unfavourable protective conditions during the first year of its existence.
With the filling of the reservoir a new biotope emerged — a shallow island zone, which was more productive than other habitats of ducks and was of promise with regard to the increase in the numbers of waterfowl.
A sharp rise in the number of formerly nesting bird species and the appearance of a considerable of species not previously encountered in the second year of the existence-of the reservoir (although the living conditions were similar in the first and second years) is the result of bird migration after nesting. Having discovered new places with good sources of food and protection in the autumn of 1965, the birds selected them for nesting in the spring of 1966.